High photoreactivity of chromophoric dissolved organic matter derived from Ulva prolifera and Sargassum - Zhang, Yong; Fang, Kaili; Liu, Mengmeng; Liu, Jihua; Zhao, Xiaobo; Zhai, Weidong; Zhang, Hongsheng; Wang, Xiaotong; Xie, Huixiang (Frontiers in Marine Science, 2024)
The epipelagic macroalgae of Ulva prolifera and Sargassum are the primary contributors to widespread seaweed tides globally. Both ocean plants release large amounts of chromophoric dissolved organic matter (CDOM) into the surrounding seawater. The photochemical reactivity of this CDOM, however, has not been adequately addressed. In this study, we extracted CDOM from Ulva prolifera and Sargassum, examined their ultraviolet (UV)-visible absorption characteristics, and quantified their broadband apparent quantum yields (AQY) of absorbance photobleaching and photomineralization (in terms of CO2, CO, and CH4 photoproduction). On a per-unit-weight basis, Sargassum leached 3.5 times more CDOM than did Ulva prolifera in terms of the absorption coefficient averaged over 254–500 nm. Both Ulva prolifera and Sargassum CDOM were characterized by quasi-exponential decay absorption spectra, with Sargassum CDOM exhibiting a distinct shoulder over 310–350 nm suggestive of mycosporine amino acids. The Sargassum CDOM had a higher photobleaching AQY but lower photomineralization AQYs compared to Ulva prolifera CDOM. The photobleaching and photomineralization AQYs of both macroalgal CDOM are, however, orders of magnitude higher than those of CDOM in various natural waters. Potential photoproduction rates of CO2 and CO from the Ulva prolifera CDOM and Sargassum CDOM during the bloom periods are several times to orders of magnitude higher than the air-sea fluxes of these gases in the absence of the macroalgae. This study demonstrates that CDOM released by Ulva prolifera and Sargassum is extremely prone to photobleaching and photomineralization, rendering floating mats of these plants in oceans as potential “hotspots” of greenhouse gas emissions to the atmosphere. This photochemical feedback should be considered when assessing ocean afforestation as a CO2 removal approach to mitigate climate warming.